Central nervous system tumour diagnosis in pediatric population – the role of an ophthalmologist and the utility of visual evoked potentials - Urban, Beata; Michalczuk, Marta; Michalczuk, Grzegorz; Szumiński, Michał; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objective : To determine possible alterations of P100 and P1 amplitudes and latencies in school-aged children with a history of a central nervous system tumour. Material and methods : The pattern visual evoked potential and flash visual evoked potential testing was performed in 42 school-aged children: 15 patients with a history of the central nervous system tumour (mean age of 13.44 ± 2.41 years and 13.75 ± 2.29 years, respectively) and 27 healthy subjects as a control group (mean age 11.84 ± 1.44 years, and 14.78 ± 4.26 years, respectively). Results : P100 amplitudes of pattern visual evoked potentials were statistically decreased in the study group as compared to the control group. The only statistically signifcant difference between the study group and the controls was latencies recorded from O1 in 15-minute stimuli. P2 amplitudes of flash visual evoked potentials were decreased and latencies were increased in the study group, however, the differences were not statistically significant. Conclusions : Visual evoked potential alterations can be a sign of functional disturbances of the visual system in patients with any central nervous system tumour. Therefore, a diagnostic process of a central nervous system tumour should include a thorough ocular exam, even in patients with normal visual acuity.